LEGALITAS ALIH FUNGSI KAWASAN HUTAN UNTUK PARIWISATA HORTIKULTURA MENURUT UU NO. 41 TAHUN 1999 TENTANG KEHUTANAN: Legality of Forest Area Conservation for Horticultural Tourism according to Law Number 41/1999 on Forestry - Jerry Iriawan; Irene Mariane (Faculty of Law, Universitas Trisakti, 2025)
The conversion of forest areas to non-forestry land for horticultural tourism activities is one of the important issues in environmental policy and regional development. The formulation of the problem is how the legality of the conversion of forest areas for the development of horticultural tourism according to Law No. 41 of 1999 concerning Forestry? The research method used is normative juridical, descriptive in nature, using secondary data, and deductive inference. The results of the discussion and conclusions show that the legality of forest area conversion for the development of horticultural tourism is regulated in Article 19 of Law No. 41 of 1999 concerning Forestry. Changes in the designation of forest areas are possible through the mechanism of release or change of function, provided that they fulfil the administrative and ecological requirements determined by the government. However, in practice, this process often leads to conflicts between the interests of environmental preservation and regional economic development. Therefore, its legality is highly dependent on compliance with legal procedures as well as guarantees that it does not damage the ecological functions of the forest.